Pengaruh Sales Growth, Capital Intensity, dan Komisaris Independen Terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang terdaftar di BEI Periode 2017-2021 - Cahaya, Sintia; Prasetya, Eka Rima (UNPERBA, 2024)
The purpose of this research is to determine the effect of sales growth, capital intensity, and independent commissioner on tax aggressive in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2021. The methodology used in this study is quantitative. The sampling techniques used was purposive sampling and a sample was obtained in this study, which was a total of 100 data. The analysis methods used are descriptive statistical analysis, classical assumption test, multiple regression analysis, determinant coefficient test, F test, and T test with the help of Eviews9 software. Based on the results of data analysis, we find that there is simultaneously effect between Sales Growth, Capital Intensity,and independent commissioner on Tax Aggressiveness. This study also finds that Sales growth have a impact on Tax Aggressiveness, while Capital Intensity and Independent Commissioner has a no impact on Tax Aggressiveness.